"I Am India Shining": The Investor-Citizen and the Indelible Icon of Good Times. Issue 3 (12th August 2016) - Kaur, Ravinder
Abstract : This article is an against-the-grain reading of the highly publicized failure of the 2004 India Shining campaign. Aimed at the Indian publics, this mega-publicity spectacle sought to communicate the success of neoliberal reforms in transforming India from a developing nation to a lucrative emerging market in the global economy. Rather than uplift the mood of the nation, the campaign brought to the surface the underlying acrimony and exclusion experienced by a vast majority of the population. I argue that the discourse of India Shining's failure misreads the electoral defeat of the Bharatiya Janata Party as the failure of the neoliberal project of economic reforms. In fact, the India Shining images helped popularize the reforms at an unprecedented mass scale that until then had largely been limited to elite policy debates and reform packages. Instead, the discontent accrued by those excluded from the good times seemingly ushered in by the reforms, and not the reforms per se. The India Shining controversy also allows us to witness a new form of investor-citizenship shaped around the language and logic of loss and profits. The very edifice of failure makes apparent the shift to a capitalist dream world and the withering away of the old order in post-reform India.